Quorum‐sensing regulator RhlR but not its autoinducer RhlI enables Pseudomonas to evade opsonization - Haller, Samantha (EMBO Rep, 2018)
When Drosophila melanogaster feeds on Pseudomonas aeruginosa, some bacteria cross the intestinal barrier and eventually proliferate in the hemocoel. This process is limited by hemocytes through phagocytosis. P. aeruginosa requires the quorum‐sensing regulator RhlR to elude the cellular immune response of the fly. RhlI synthesizes the autoinducer signal that activates RhlR. Here, we show that rhlI mutants are unexpectedly more virulent than rhlR mutants, both in fly and in nematode intestinal infection models, suggesting that RhlR has RhlI‐independent functions. We also report that RhlR protects P. aeruginosa from opsonization mediated by the Drosophila thioester‐containing protein 4 (Tep4). RhlR mutant bacteria show higher levels of Tep4‐mediated opsonization, as compared to rhlI mutants, which prevents lethal bacteremia in the Drosophila hemocoel. In contrast, in a septic model of infection, in which bacteria are introduced directly into the hemocoel, Tep4 mutant flies are more resistant to wild‐type P. aeruginosa, but not to the rhlR mutant. Thus, depending on the infection route, the Tep4 opsonin can either be protective or detrimental to host defense.